Decreased N-TAF1 expression in X-linked dystonia-parkinsonism patient-specific neural stem cells - Naoto Ito; William T. Hendriks; Jyotsna Dhakal; Christine A. Vaine; Christina Liu; David Shin; Kyle Shin; Noriko Wakabayashi-Ito; Marisela Dy; Trisha Multhaupt-Buell; Nutan Sharma; Xandra O. Breakefield; et al. (The Company of Biologists, 2016)
X-linked dystonia-parkinsonism (XDP) is a hereditary neurodegenerative disorder involving a progressive loss of striatal medium spiny neurons. The mechanisms underlying neurodegeneration are not known, in part because there have been few cellular models available for studying the disease. The XDP haplotype consists of multiple sequence variations in a region of the X chromosome containing TAF1, a large gene with at least 38 exons, and a multiple transcript system (MTS) composed of five unconventional exons. A previous study identified an XDP-specific insertion of a SINE-VNTR-Alu (SVA)-type retrotransposon in intron 32 of TAF1, as well as a neural-specific TAF1 isoform, N-TAF1, which showed decreased expression in post-mortem XDP brain compared with control tissue. Here, we generated XDP patient and control fibroblasts and induced pluripotent stem cells (iPSCs) in order to further probe cellular defects associated with this disease. As initial validation of the model, we compared expression of TAF1 and MTS transcripts in XDP versus control fibroblasts and iPSC-derived neural stem cells (NSCs). Compared with control cells, XDP fibroblasts exhibited decreased expression of TAF1 transcript fragments derived from exons 32-36, a region spanning the SVA insertion site. N-TAF1, which incorporates an alternative exon (exon 34'), was not expressed in fibroblasts, but was detectable in iPSC-differentiated NSCs at levels that were ∼threefold lower in XDP cells than in controls. These results support the previous findings that N-TAF1 expression is impaired in XDP, but additionally indicate that this aberrant transcription might occur in neural cells at relatively early stages of development that precede neurodegeneration.